Entre política identitaria y narrativas autobiográficas. Restituciones digitales de un proyecto de documentación lingüística en Bolivia (Proyecto DoBeS Yurakaré 2006-2011) - Vincent Hirtzel (Journal de la Société des Américanistes)
The Yurakaré of the Bolivian Amazon have influenced, in different ways, the DoBeS language documentation project in which the author participated. On the one hand, the material collected has been digitally returned on hard disks to several of their political and educational organizations. This global restitution is part of a process of building a “national” Yurakaré identity, which results from the structural transformations of Bolivia into a Plurinational State. In addition, this documentation project benefited from the collaboration of three speakers who agreed to record material of an autobiographical nature. We will focus here on this sub-corpus in relation to the challenges of global restitution; in terms of its content, target audience and circulation. This comparison brings to light a sample of various reflexive experiments which will be the subject of a comparative sketch with other examples of DoBeS projects that took place in Brazil (Upper Xingu).